Experimental Substantiation for Applying Cryopreserved Preparations of Embryofetoplacental Complex to Correct Thyroid Gland Pathologies Report 2. The Effect of Human Fetal Cell Suspension Biopreparation on Functional Activity of Rabbit Thyroid Gland - Malova, N. G.; Yurchenko, T. N.; Bozhko, T. S.; Komarova, I. V.; Strona, D. V.; Solonets, Yu. M.; Chujkova, V. I. (Problems of Cryobiology and Cryomedicine, 2007)
The xenotransplantation effect of cryopreserved biopreparation of human fetal tissue suspension (FTS) on thyroid gland (TG) functional activity in rabbits with a suppressed thyroid function (an experimental mercazolil hypothyrosis) was investigated. A normalising effect of the therapy performed on the experimental animals’ thyroid system was noted. The FTS stimulating effect and its maximum were observed by the second week and second month after introduction, correspondingly. The hormonogenesis stimulation in TG was established as realising under a direct FTS influence on thyroid parenchyma with no central regulation mechanism participation; a dominating effect of preparation on thyroxin biosynthesis with no significant change in T3 level.